KERJASAMA BIDANG PERADILAN ANTAR NEGARA DALAM RANGKA UPAYA PENYERAGAMAN PRANATA HUKUM ANTAR BANGSA - Eman Suparman (Jurnal Hukum dan Peradilan, 2012)
Applicability of the rules of the positive law of a country is limited by territorial boundaries that country. While the legal relationship that lasted between members of the community of nations always occurs and exceeds the limits of the territorial sovereignty of the state law. Therefore, the national law of the countries should continue to be pursued in order to be able to answer a variety of transnational issues that exist. The effort is certainly not intended to be uniform throughout the internal legal system of sovereign states, but merely an attempt to harmonize the rules of international private law. While problem solving for issues specific civil law will be made by the judicial bodies of each country. In order to accommodate this reality, is a conditio sine qua non for Indonesia to consider measures to make international agreements in order to enrich the rules of civil procedure law court. The problem, at least to face the coming force of AFTA in the ASEAN region should be harmonization between the legal systems of the individual ASEAN member countries. If not, the difficulty for the difficulties to be faced every country, when the demands of the right form of execution verdict handed down in a country can not be implemented in other sovereign nations. The situation is certainly less beneficial terms of economic cooperation. Therefore, the establishment of a model law for a convention in the form of the ever pursued by countries in the European region, reasonably considered to be a model in drafting the ASEAN convention. At least these efforts will support the objective of allied countries to achieve harmonization of laws between countries in the ASEAN region. Keywords: cooperation in judicial, legal institutions, harmonization